PERANCANGAN PENATAAN KAWASAN KAMPUS II UIN ALAUDDIN DI SAMATA KABUPATEN GOWA - AS, Zulkarnain; Jumawan, Faris; Manga, Muh. Rante (Teknosains: Media Informasi Sains dan Teknologi, 2017)
As one of the major campuses in the region Mamminasata, UIN Alauddin showed a very significant improvement. Since moving into second campus located in Samata Gowa in 2010, Alauddin State Islamic University is growing from day to day. Starting from the development of lecturers, employees, increasing the number of students to the fulfillment of the facility, as well as the improvement of the environment in the campus area. But in an effort to meet the needs of the facility and the environmental improvements there beberpa obstacles that must be faced. The increasing need some academic facilities, institutional, and environmental concomitant increase in the number of lecturers, employees and the number of students. Thus it is necessary to design the arrangement of the campus area in anticipation of a surge in the need of parking, classrooms and administration, sports facilities and places of worship, as well as the need for open green space. Structuring is done in the form of relocation and renovation as well as the addition of some construction of new facilities by utilizing the potential locations are in areas of the campus.